Microdisk Resonator With Negative Thermal Optical Coefficient Polymer for Refractive Index Sensing With Thermal Stability - Tao Ma; Jinhui Yuan; Feng Li; Lei Sun; Zhe Kang; Binbin Yan; Qiang Wu; Xinzhu Sang; Kuiru Wang; Heng Liu; Fang Wang; Bo Wu; et al. (IEEE Photonics Journal, 2018)
In this paper, we propose a microdisk resonator with negative thermal optical coefficient (TOC) polymer for refractive index (RI) sensing with thermal stability. The transmission characteristics and sensing performances by using quasi-TE01 and quasi-TM01 modes are simulated by a three-dimensional finite element method. The influences of the TOC, RI, and thickness of the polymer on the sensing performances are also investigated. The simulation results show that the RI sensitivity Sn and temperature sensitivity ST with different polymers are in the ranges of 25.1–26 nm/RIU and 67.3–75.2 pm/K for the quasi-TE01 mode, and 94.5–110.6 nm/RIU and 1.2–51.3 pm/K for the quasi-TM01 mode, respectively. Moreover, figure-of-merit of the temperature sensing for the quasi-TM01 mode is in the range of 2 × 10−4–8 × 10–3, which can find important application in the implementation of the adiabatic devices.